Lived Islam in South Asia : adaptation, accommodation and conflict - Ahmad, Imtiaz, 1940-; Reifeld, Helmut; Konrad-Adenauer-Stiftung; Conference Entitled'Lived Islam in South Asia : Adaptation, accommodation and Conflict' ( 2002 : Goa, India) (New Delhi : Social Science Press, 2004)
Contributed seminar papers
Papers from a conference initiated and organized by the Konrad Adenauer Foundation
Keywords: Islam -- South Asia -- Congresses; Muslims -- South Asia -- Congresses; Hinduism -- Relations -- Islam -- Congresses; Islam -- Relations -- Hinduism -- Congresses